2018
DOI: 10.1042/bcj20170418
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in Sox2 spatio-temporal expression promote the second cell fate decision through Fgf4/Fgfr2 signaling in preimplantation mouse embryos

Abstract: Oct4 and Sox2 regulate the expression of target genes such as Nanog, Fgf4, and Utf1, by binding to their respective regulatory motifs. Their functional cooperation is reflected in their ability to heterodimerize on adjacent cis regulatory motifs, the composite Sox/Oct motif. Given that Oct4 and Sox2 regulate many developmental genes, a quantitative analysis of their synergistic action on different Sox/Oct motifs would yield valuable insights into the mechanisms of early embryonic development. In the present st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 60 publications
4
19
0
Order By: Relevance
“…Recent studies reported that quantitative properties of SOX2 and OCT4 such as expression levels or DNA-binding properties are predictive of cell fate decisions at the four-cell stage (White et al, 2016;Goolam et al, 2016). Differences in SOX2 concentrations were also shown to change its enhancer binding profile (Mistri et al, 2018), however whether this translates into differences in cell fate commitment is unknown. SOX2 and OCT4 were also reported to play antagonistic roles in the differentiation of ES cells towards the neuroectodermal (NE) and mesendodermal (ME) fates (Zhao et al, 2004;Thomson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that quantitative properties of SOX2 and OCT4 such as expression levels or DNA-binding properties are predictive of cell fate decisions at the four-cell stage (White et al, 2016;Goolam et al, 2016). Differences in SOX2 concentrations were also shown to change its enhancer binding profile (Mistri et al, 2018), however whether this translates into differences in cell fate commitment is unknown. SOX2 and OCT4 were also reported to play antagonistic roles in the differentiation of ES cells towards the neuroectodermal (NE) and mesendodermal (ME) fates (Zhao et al, 2004;Thomson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although Fgf4 is the first gene displaying a bimodal expression within the early ICM, the questions, why this ligand is expressed in just a few ICM cells and whether its expression is stable or fluctuates, require further studies. The recent report of Mistri et al, has indicated SOX2 and its increasing expression level in the emerging inner cells as the main driver of the earliest heterogeneity within the ICM (Mistri et al, 2018). Regardless of the FGFR1 expression, a subpopulation of ICM cells starts to express FGFR2 (Kang et al, 2017).…”
Section: The Role Of Fgf4/erk Pathway In Maturation Of the Mouse Epibmentioning
confidence: 99%
“…However, single-cell resolution image analysis revealed that the highest ability of individual ICM cells to respond to the FGF cascade stimulation or inhibition occurs between E3.25 to E3.5 and corresponds to the period when double-positive cells, expressing both GATA6 and NANOG first protein that exhibits a bimodal expression within the ICM cells of the E3.25 blastocyst (32-50 cells), preceding the segregation of EPI and PE precursor cells at E3.5 (Krupa et al, 2014;Ohnishi et al, 2014). The question whether this heterogenous expression of FGF4 is a result of intrinsic stochastic fluctuations in its expression levels or the origin of ICM cells (from the first or second round of the asymmetric divisions giving rise to the embryonic inner cells) remains controversial (Morris et al, 2010;Yamanaka et al, 2010;Morris et al, 2013;Krupa et al, 2014;Mistri et al, 2018). Since the inner cells contributing to the ICM are generated in different time points, it has been proposed that those internalized in the first round (at the 8-to 16-cell transition) and expressing FGF4 at a higher level are biased to form the EPI, whereas those arising during the second round (16-to 32-cell transition) and expressing more FGFR2, are biased towards the PE fate (Morris et al, 2010;Morris et al, 2013;Krupa et al, 2014).…”
Section: Fgf4 Ligand: Pattern Expression and Function In The Early Momentioning
confidence: 99%
See 1 more Smart Citation
“…A dichroic mirror (560DRLP) and bandpass emission filters (500-550nm for Alexa 488/GFP and 607-683nm for Atto 565/mCherry, (Chroma Technology, VT) were used to separate the excitation light coming from the fluorescence emission. A standard calibration approach was used to determine the absolute concentration of the fusion proteins in the crude nuclear lysate (Mistri, Devasia et al 2015, Mistri, Arindrarto et al 2018. Appropriately chosen dyes with known diffusion coefficients were employed to determine the confocal volume accurately.…”
Section: Fluorescence Correlation and Cross-correlation Spectroscopy mentioning
confidence: 99%